Pengaturan Impor Sampah Plastik Di Indonesia - Lendry Hendrik; Lucia Charlota Octovina Tahamata; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Law has an important rolf in life, because without law, there willbe no order and peacein people’s lives, including teh export-import process of plastic waste, therefore rules are made to regulate it.Purposes of the Research: Based on background, author aim to identify the regulation of plastic waste import in Indonesia.Methods of the Research: Method used is the normative juridical research method with statue aprroach and conceptual aprroach.Results of the Research: Based on author’s research, regulation of plastic waste in Indonesia is regulated at various levels, including law number 32 of 2009 concerning protection and management of the envitonmen, articel 69 paragraph (1) letter c explixitly prohibited everyone from entering organic waste from foreign country to Indonesia’s enviromental media.